PARTITION COEFFICIENTS OF NB AND TA BETWEEN RUTILE AND ANHYDROUS HAPLOGRANITE MELTS - Horng W.Sh.; Hess P.C. (My University, 2000)
Partition coefficients (D) for Nb and Ta between rutile and haplogranite melts in the K2O-Al2O3-SiO2 system have been measured as functions of the K2O/Al2O3 ratio, the concentrations of Nb2O5 and Ta2O5, the temperature, in air and at 1 atmosphere pressure. The Ds increase in value as the K* [K2O/(K2O + Al2O3)] molar ratio continuously decreases from highly peralkaline [K* ~ 0.9] to highly peraluminous [K* ~ 0.35] melts. The D values increase more dramatically with a unit decrease in K* in peraluminous melts than in peralkaline melts. This compositional dependence of Ds can be explained by the high activity of NbAlO4 species in peraluminous melts and the high activity of KONb species (or low activity of NbAlO4 species) in peralkaline melts. A coupled substitution, Al+3 + Nb+5 (or Ta+5) = 2Ti+4, accounts for the Ds of Nb (Ta) being much greater in peraluminous melts than in peralkaline melts because this substitution allows Nb (Ta) to enter into the rutile structure more easily. The Ds of Ta between rutile and melt are greater than those of Nb at comparable concentrations because the molecular electronic polarizability of Ta is weaker than that of Nb. The Nb+5 with a large polarizing power forms a stronger covalent bond with oxygen than Ta+5 with a small polarizing power. The formation of the strong bond, Nb-O, distorts the rutile structure more severely than the weak bond, Ta-O; therefore, it is easier for Ta to partition into rutile than for Nb. These results imply that the utilization of the Nb/Ta ratio in liquid as a petrogenetic indicator in granitic melts must be done with caution if rutile (or other TiO2-rich phases) is a liquidus phase. The crystallization of rutile will increase the Nb/Ta ratio of the residual liquid because the Ds of Ta between rutile and melts are greater than those of Nb.